THE ACADEMIC LITERACY OF SIXTEEN-SEVENTH GRADERS OF AN ENGLISH IMMERSION JUNIOR HIGH SCHOOL IN SEMARANG - Rajagukguk, Th. Ervina Boru; Agustien, Helena I. R.; Mujiyanto, Yan (Language Circle: Journal of Language and Literature, 2017)
This research was conducted to observe sixteen seven graders of Mondial Junior High Schoolâ academic literacy in their academic written texts. The participants were accustomed to using English at their school. Yet, when they had to produce academic texts, the texts were produced in the level of knowledge-telling, which lacked time to plan and to set the goals. The data of this study were taken from their quizzes and final test of four subjects with different genres of texts. Because the quizzes and final test were graded, the quality of the data is ensured. The analysis was observed qualitatively from three dimensions, i.e. the linguistic, cognitive, and socio-cultural dimensions of literacy. To describe each dimension, there were some descriptors to guide the analysis process. The result shows that in general, the sixteen learnersâ academic literacy was fairly good. However, some parts of the dimension of academic literacy such as the linguistic and socio-cultural dimensions should be improved in order to master the holistic dimensions of literacy. The learners should be introduced to some genres of texts which were considered new for them such as explanation text. Their mastery towards past tense should also be improved.